CRS and HIPEC for pancreatic ductal adenocarcinoma with peritoneal metastases: a case report - Amin-Tai, Hizami; Adznan, Muhammad Ash-Shafhawi; Canda, Aras Emre; Yılmaz, Hüseyin Cahit; Kılıç, Murat; Terzi, Mustafa Cem (Surgical Society of North Greece, 2023)
Background: Pancreatic ductal adenocarcinoma (PDAC) is aggressive, with more than 80% present with metastatic disease, and an overall survival of less than a year with systemic chemotherapy treatment. Cytoreductive surgery (CRS) and intraperitoneal chemotherapy are two treatment modalities being explored to improve the survival rates of these patients. Case presentation: A 45-year-old man presented with epigastric pain, mass, and weight loss. Investigations revealed a pancreatic tumour with liver and extensive peritoneal metastases. After 18 cycles of chemotherapy, there was significant disease regression which allowed CRS and HIPEC to be performed. HIPEC, PIPAC, and repeated intraperitoneal liquid chemotherapy have been shown to be safe. Longer survival and reduced disease related complications are among the advantages seen in published data. Conclusion: Complete cytoreduction and HIPEC, repeated cycles of either intraperitoneal chemotherapy or PIPAC, are associated with longer survival and reasonable adverse effects. Patients diagnosed with PDAC and peritoneal metastases should be considered for these treatment strategies.